Enhance students’ engineering ability based on virtual three coordinate design and measurement - Wang Biao; Wu Nannan; Zhao Fuyuan; Ma Yuhan; Zhang Yuxuan; Wang Yonghong; Zhang Jin (SHS Web of Conferences, 2024)
The three coordinate measuring machine (CMM) are increasingly widely used, but because of their high price, not easy to portable and other drawbacks, it is difficult to be widely used in university teaching procedures. Therefore, some disciplines such as measurement and control theories, measurement methods behind of the CMM are hard to well understood, which require students to have strong engineering ability. In order to solve the problem, the paper presents a virtual CMM way to improve the students engineering experience that improve the quality of course teaching as an assist tool. Firstly, use 3ds Max to model CMM, including probe, guide rail, frame, etc. Secondly,after the modeling development is completed, Hololens is used as a platform to develop scene interaction functions using Unity and c# scripts, that is, the connection between virtual scenes and students.Thirdly, in the virtual interface, students control the probe by the button to record and measure the coordinates of the object to be measured, and complete the measurement experiment. Students can master the measuring principle and measuring process of CMM faster through Hololens. So that students have a more intuitive understanding of CMM and are no longer limited by the traditional CMM teaching, it is of great significance to the cultivation of students’ engineering ability.